Seasonal variation in sleep homeostasis in migratory geese: a rebound of NREM sleep following sleep deprivation in summer but not in winter. Issue 4 (21st November 2020) - van Hasselt, Sjoerd J; Mekenkamp, Gert-Jan; Komdeur, Jan; Allocca, Giancarlo; Vyssotski, Alexei L; Piersma, Theunis; Rattenborg, Niels C; Meerlo, Peter
Abstract: Sleep is a behavioral and physiological state that is thought to serve important functions. Many animals go through phases in the annual cycle where sleep time might be limited, for example, during the migration and breeding phases. This leads to the question whether there are seasonal changes in sleep homeostasis. Using electroencephalogram (EEG) data loggers, we measured sleep in summer and winter in 13 barnacle geese ( Branta leucopsis ) under semi-natural conditions. During both seasons, we examined the homeostatic regulation of sleep by depriving the birds of sleep for 4 and 8 h after sunset. In winter, barnacle geese showed a clear diurnal rhythm in sleep and wakefulness. In summer, this rhythm was less pronounced, with sleep being spread out over the 24-h cycle. On average, the geese slept 1.5 h less per day in summer compared with winter. In both seasons, the amount of NREM sleep was additionally affected by the lunar cycle, with 2 h NREM sleep less during full moon compared to new moon. During summer, the geese responded to 4 and 8 h of sleep deprivation with a compensatory increase in NREM sleep time. In winter, this homeostatic response was absent. Overall, sleep deprivation only resulted in minor changes in the spectral composition of the sleep EEG. In conclusion, barnacle geese display season-dependent homeostatic regulation of sleep. These results demonstrate that sleep homeostasis is not a rigid phenomenon and suggest that some species may tolerate sleep loss under certain conditions or during certain periods of the year.